Efek Protektif Tepung Pisang, Singkong dan Jagung terhadap Hepatotoksisitas Tikus Jantan Malnutrisi: Protective Effect of Banana, Cassava, and Corn Flours on Hepatotoxicity of Malnourished Male Rats - Mohammed, Najib; Lestari, Sri Rahayu; Susanto, Hendra; Rakhmawati, Yunita (Universitas Airlangga, 2024)
Background: Malnutrition-induced hepatotoxicity is defined as liver damage caused by insufficient nutrition, which results in oxidative stress and damage to liver cells. Objectives: The present study aimed to investigate the protective effects of banana, cassava, and corn flours on hepatotoxicity induced by malnutrition in male rats. Methods: Twenty-four male rats were divided into six groups (n=4): (1) rats received 30 g/rat normal feed daily for 45 days; (2) rats received 30 g malnutrition feed daily for 45 days; rats received 30 g/rat malnutrition feed daily for 15 days and then treated with normal feed (3), banana flour (4), cassava flour (5), and corn flour (6), for 30 days. The malnutrition groups received a diet with protein deficiency for 15 days, then were treated with a diet according to each treatment group. The liver enzymes were analyzed, including aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels. Furthermore, the liver's histopathological changes in each group were evaluated using Hematoxylin eosin staining. Results: The AST levels in malnourished male rats significantly (p<0.05) increased (240.75±67.23 U/L) compared to the control group (170.00±33.52 U/L). While, the ALT levels (66.75±12.69 U/L) were decreased compared to the control group (98.75±26.61 U/L). Furthermore, malnutrition diet in rats caused significant changes in liver histology, including inflammatory cell infiltration, necrosis, congestion of the central vein, cytoplasmic vacuolization, and widened hepatic sinusoid. Interestingly, normalized AST and ALT levels and improved liver histology were observed in malnourished rats after receiving normal feed and flour of banana, cassava, and corn. Conclusions: Banana, cassava, and corn flours exhibited hepatoprotective activity on malnutrition-induced hepatotoxicity in malnourhised male rats.